The Influence of Al3+ Metal Ion in AlCl3 Compound On α- Amylase Enzyme Activity - Choirul Chasanah; Das Salirawati (Universitas Negeri Yogyakarta, 2021)
The influence of Al3+ metal ion in AlCl3 towards α-amylase enzyme activity have been studied. The activity of the α-amylase enzyme on potato starch substrate was determined using the DNS method (3,5-dinitrosalicylic acid) at optimum conditions. The data analysis was conducted in a descriptive qualitative manner. The results obtained that α-amylase enzyme activity with potato starch substrate was optimum at 20 mg/mL with pH 7.2, incubation temperature 37˚C, incubation time 15 minutes, and enzyme concentration of 40 mg/mL with an average enzyme activity value of 0.0079 mg/mL/minute at 37˚C. However, after the addition of Al3+ metal ion, the average value of enzyme activity decreased. These means that empirically Al3+ metal ion has a tendency to be inhibitory to the α-amylase enzyme activity on potato starch substrates.